Digital-Based Education in the Era of Society 5.0: Synergy of Digital Literacy and Learning Motivation to Improve Student Learning Outcomes - Wahidin, Wahidin; Az Zahro, Fatimah; Hadiansyah, Chairil Fajar; Ismail, Achmad Taufik (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2025)
This study examines the relationship and combined influence of digital literacy and learning motivation on the academic performance of Islamic Education Management (MPI) students in two until six semesters during the Society 5.0 era. Using a quantitative correlational and multiple regression design, 98 students were selected as samples. Instruments included a digital literacy questionnaire covering eight dimensions of competence and a learning motivation questionnaire adapted from the MSLQ. Learning outcomes were measured by students’ Grade Point Average (GPA). Data were analyzed using descriptive statistics, Pearson correlation, and multiple linear regression with SmartPLS 4.0. The findings reveal that (1) digital literacy has a positive and significant relationship with learning outcomes; (2) learning motivation also positively and significantly correlates with learning outcomes; and (3) both variables jointly exert a significant effect on students’ learning outcomes. The R-square value indicates that digital literacy and motivation together make a substantial contribution in explaining variations in academic achievement. The study concludes that synergy between digital competence and strong learning motivation is crucial in digital-based education to enhance MPI students’ performance. Practically, it underscores the need for integrated programs that strengthen digital literacy and foster intrinsic motivation among students.